2019
DOI: 10.1126/sciadv.aax0262
|View full text |Cite
|
Sign up to set email alerts
|

Learning to read recycles visual cortical networks without destruction

Abstract: Learning to read is associated with the appearance of an orthographically sensitive brain region known as the visual word form area. It has been claimed that development of this area proceeds by impinging upon territory otherwise available for the processing of culturally relevant stimuli such as faces and houses. In a large-scale functional magnetic resonance imaging study of a group of individuals of varying degrees of literacy (from completely illiterate to highly literate), we examined cortical responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 37 publications
14
63
1
Order By: Relevance
“…This competitive word-face effect was observed both in individuals who acquired literacy in childhood and in those who acquired literacy in adulthood, a finding that speaks to the possibility of ongoing competition in cortex over the lifespan. Somewhat at odds with these findings of a competitive effect with voxels in the LH being increasingly tuned to words, and subsequently voxels in the RH increasing in proportion to reading scores, is a new study conducted with a large number of individuals of varying degrees of literacy (Hervais-Adelman et al., 2019). The findings revealed that the acquisition of literacy does indeed recycle existing object representations, but there was no concomitant impinging on other stimulus categories, and face activation remained detectable in the left VOTC even after word acquisition.…”
Section: Empirical Support For the Distributed Account Of Hemisphericmentioning
confidence: 99%
“…This competitive word-face effect was observed both in individuals who acquired literacy in childhood and in those who acquired literacy in adulthood, a finding that speaks to the possibility of ongoing competition in cortex over the lifespan. Somewhat at odds with these findings of a competitive effect with voxels in the LH being increasingly tuned to words, and subsequently voxels in the RH increasing in proportion to reading scores, is a new study conducted with a large number of individuals of varying degrees of literacy (Hervais-Adelman et al., 2019). The findings revealed that the acquisition of literacy does indeed recycle existing object representations, but there was no concomitant impinging on other stimulus categories, and face activation remained detectable in the left VOTC even after word acquisition.…”
Section: Empirical Support For the Distributed Account Of Hemisphericmentioning
confidence: 99%
“…Despite this, part of the human cerebral cortex seems to be specialized for reading. For example, during reading acquisition, cortical surface in the left fusiform gyrus that is originally devoted to the processing of visual objects (and faces in particular) becomes tuned to orthographic material [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the site of the VWFA does not activate strongly to written words in illiterates (Dehaene et al, 2010;Hervais-Adelman et al, 2019) and in typical children before they learn to read (Dehaene-Lambertz et al, 2018), its under-activation in poor readers may simply reflect the lack of reading practicein other words, it might be a consequence rather than a cause of the reading deficit. Dyslexia is likely to be a heterogeneous deficit with a variety of different causes, including a phonological deficit in many children, but also visual attentional deficits, plausibly anywhere along the complex processing chain that leads from print to sound and meaning (Friedmann et al, 2010;Paulesu et al, 2014;Valdois et al, 2012).…”
Section: A Universal Neural Phenotype For Reading Disabilitymentioning
confidence: 97%
“…Several studies in alphabetic languages suggest that, during reading acquisition in children, words and faces may compete for cortical territory within the left fusiform gyrus (Centanni et al, 2018;Dehaene-Lambertz et al, 2018;Hervais-Adelman et al, 2019;Li et al, 2013;Ventura et al, 2013). Given the complexity of Chinese characters and their frequently reported bilateral activation, we investigated how face activation might be differently modulated by different reading abilities in Chinese and French children.…”
Section: Introductionmentioning
confidence: 99%